Power Optimization of Electric Developments in Diesel Power Plant for the Electrical Energy Sources using Dynamic Programming Algorithm - Haq, Sigit Prasetyo; Muladi, Muladi; Sendari, Siti (Universitas Negeri Malang, 2019)
The electricity need in the G4 Building at the State University ofMalang was more than 85 kVA. All electrical devices could beactivated; but when the energy source was inactive, all electricityrequirements were transferred to the diesel power plant (DPP).However, the electrical capacity of DPP was only 20 kVA;therefore, it was necessary to optimize the electrical power load sothat the DPP energy could be absorbed optimally using the roomscheduling and electrical devices priority systems. The DynamicProgramming Algorithm was embedded in the power optimizationsystem to help optimize the work. The power optimization prototypewas used to simulate the 1st floor of the G4 Building’s condition.The system consisted of a controller, a central controller, and auser interface. the controller comprised of a current sensor,microcontroller, and a relay. The central controller consisted ofRaspberry Pi 3 hardware that was installed as the server to answerthe HTTP request from the controller and user interface. The userinterface was displayed in a dynamic web to ease the user inmanaging the electrical devices and entering the room usageschedule. The power optimization system managed the electricalenergy from DPP by turning on the electrical devices according tothe priority value. The power optimization system tests were dividedinto six problems, of which each stage had an error value of 0%.